MANAGING STUDENT RESEARCH ACTIVITY IN AN INNOVATIVE EDUCATIONAL CLUSTER: SCIENTIFIC AND THEORETICAL FOUNDATIONS (World Bulletin of Education and Learning, 2025)
Contemporary educational reforms emphasize the development of student research competencies and innovation-oriented learning. This article examines the scientific and theoretical foundations for managing student research activity within an innovative educational cluster environment, which links pedagogical universities and general schools. Through analysis of policy documents and pedagogical literature, we identify key concepts, models, and pedagogical conditions that support effective research engagement by students. The findings highlight that inquiry-based learning has deep historical roots and is reaffirmed by modern educational theory as a crucial method for developing critical thinking and problem-solving skills. We compare various frameworks of organizing student research (functional and structural models, problem-based and project-based approaches) and distill common stages (problem identification, hypothesis formation, experimentation, analysis, and presentation) essential to the research process. We also discuss principles for guiding student inquiry (e.g. ensuring genuine interest, fostering both convergent and divergent thinking) and the teacher’s evolving role as a facilitator-researcher. Furthermore, we explore how a pedagogical innovation cluster – a cooperative network of teacher education institutions and schools – can create an integrative environment that nurtures research skills through collaborative projects, mentorship, and shared resources. This cluster approach is presented as a viable mechanism to bridge theoretical knowledge with practical inquiry, thereby preparing future teacher-researchers and cultivating a new generation of inquisitive learners. The article concludes with implications for implementing cluster-based research education and improving educational outcomes in line with international benchmarks.
Keywords: Student research activity; Inquiry-based learning; Research competencies; Innovative educational cluster; Pedagogical collaboration; Teacher-researcher; Problem-based learning; Education reform.